THE ROLE AND NEGATIVE IMPACTS OF SOCIAL MEDIA IN SOCIETY - Saidova Madinabonu Abduhakim qizi, (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
This paper explores the dual nature of social media as a powerful communication tool and a potential source of social challenges. While social media platforms such as Facebook, Instagram, X (formerly Twitter), and TikTok have revolutionized information sharing, social interaction, and activism, they have also contributed to various negative consequences. These include the spread of misinformation, mental health issues, cyberbullying, addiction, and the erosion of face-to-face communication skills. The study examines the influence of social media on public opinion, youth behavior, and societal norms, highlighting the urgent need for digital literacy, ethical regulation, and responsible usage. The findings emphasize a balanced approach to harnessing the benefits of social media while mitigating its risks.